Vps34 regulates myofibril proteostasis to prevent hypertrophic cardiomyopathy - Hirotaka Kimura; Satoshi Eguchi; Junko Sasaki; Keiji Kuba; Hiroki Nakanishi; Shunsuke Takasuga; Masakazu Yamazaki; Akiteru Goto; Hiroyuki Watanabe; Hiroshi Itoh; Yumiko Imai; Akira Suzuki; et al. (JCI Insight, 2017)
Hypertrophic cardiomyopathy (HCM) is a common heart disease with a prevalence of 1 in 500 in the general population. Several mutations in genes encoding cardiac proteins have been found in HCM patients, but these changes do not predict occurrence or prognosis and the molecular mechanisms underlying HCM remain largely elusive. Here we show that cardiac expression of vacuolar protein sorting 34 (Vps34) is reduced in a subset of HCM patients. In a mouse model, muscle-specific loss of Vps34 led to HCM-like manifestations and sudden death. Vps34-deficient hearts exhibited abnormal histopathologies, including myofibrillar disarray and aggregates containing αB-crystallin (CryAB). These features result from a block in the ESCRT-mediated proteolysis that normally degrades K63-polyubiquitinated CryAB. CryAB deposition was also found in myocardial specimens from a subset of HCM patients whose hearts showed decreased Vps34. Our results identify disruption of the previously unknown Vps34-CryAB axis as a potentially novel etiology of HCM.